2021
DOI: 10.1038/s41398-021-01230-z
|View full text |Cite
|
Sign up to set email alerts
|

Low dose oral ketamine treatment in chronic suicidality: An open-label pilot study

Abstract: Recently, low-dose ketamine has been proposed as a rapid-acting treatment option for suicidality. The majority of studies to date have utilised intravenous (IV) ketamine, however, this route of administration has limitations. On the other hand, oral ketamine can be administered in a range of settings, which is important in treating suicidality, although studies as to safety and feasibility are lacking. n = 32 adults (aged 22–72 years; 53% female) with chronic suicidal thoughts participated in the Oral Ketamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…The Oral Ketamine Trial on Suicidality (OKTOS) is an open-label trial of sub-anesthetic doses of oral ketamine over 6 weeks. Six weeks of oral ketamine treatment in participants with chronic suicidality led to a significant reduction in suicidal ideation [ 70 ]. The authors reported that the response observed in this study is consistent with IV ketamine trials; however, the study excluded patients with acute suicidality, history of psychosis, mania/hypomania and several medical conditions, including abnormal liver function testing, history of stroke, cardiovascular disease and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The Oral Ketamine Trial on Suicidality (OKTOS) is an open-label trial of sub-anesthetic doses of oral ketamine over 6 weeks. Six weeks of oral ketamine treatment in participants with chronic suicidality led to a significant reduction in suicidal ideation [ 70 ]. The authors reported that the response observed in this study is consistent with IV ketamine trials; however, the study excluded patients with acute suicidality, history of psychosis, mania/hypomania and several medical conditions, including abnormal liver function testing, history of stroke, cardiovascular disease and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent clinical trial involving 32 patients with a history of chronic suicidal thoughts found that ketamine was associated with a reduction in suicidal ideation over a 6-week period, with over two-thirds of participants reporting a significant benefit. These effects were independent of the patients' formal diagnosis or concurrent treatment with other medications, and were associated with increased grey matter volumes in brain regions that form part of the "social pain circuit", such as the thalamus and periaqueductal gray [135,136]. Crucially, it has also been observed that the anti-suicidal effects of ketamine in humans are blocked by the administration of naltrexone, a drug that acts primarily as a µ-opioid receptor antagonist [137].…”
Section: E3 Glutamate Receptor Antagonistsmentioning
confidence: 97%
“…Regarding KET, the minimum therapeutic dose for depression is 0.5 mg kg –1 . For a person weighing 50 kg, this amounts to 25 mg ≈ 0.1 mmol KET in 40 mL spirit, i.e., 2.5 mmol L –1 KET, which can be successfully detected by the e-finger . In the case of PAR, the addition of 1 pill of Depon (500 mg of PAR) in a spirit bottle of 1 L represents 500 mg L –1 PAR and therefore the e-finger can effectively detect ultra-traces of this analgesic.…”
Section: Detection Of Drds and Par With The E-fingermentioning
confidence: 99%